Life Cycle Cost Analysis of Direct Air Capture Integrated with HVAC Systems: Utilization Routes in Formic Acid Production and Agricultural Greenhouses - Aliya Banu (17017731) (2025)
Integrating direct air capture (DAC) technology into Heating, Ventilation, and Air Conditioning (HVAC) systems offers an innovative approach to improving energy efficiency and indoor air quality in buildings while simultaneously reducing carbon emissions. This study investigates the economic feasibility of DAC integrated with HVAC by evaluating several key economic indicators including life cycle costing. Two adsorbents, Lewatit VP OC 1065 (Lewatit) and SBA-15, are evaluated within the system, for which the results indicate a significant economic advantage for SBA-15 over Lewatit. The levelized cost of the DAC with SBA-15 was found to be $202 per ton of CO2 captured, demonstrating competitive economics for this carbon capture technology. To enhance the process's economics, the captured CO2 is utilized in two key utilization pathways: low-carbon fuel and agricultural production. The first pathway explores the electrochemical conversion of CO2 into formic acid (FA). The system demonstrates strong economic potential, with an NPV of $6.41 million and a levelized cost of $0.499/kg of FA. Critical economic parameters, such as Faradaic efficiency, current density, and electrolyzer stack price, are identified and should be optimized through further research into electrolyzer design. Alternatively, the second pathway considers utilizing the captured CO2 for greenhouse CO2 enrichment, enhancing crop growth and reducing water consumption, thus addressing food security concerns. The NPV for the greenhouse system with CO2 enrichment was calculated to be $226,879, with a levelized cost of $1.13/kg of produce (tomatoes). Sensitivity analyses are performed on key economic variables, including the discount rate, electricity price, and final product selling price, to account for future market fluctuations. Other Information Published in: Journal of Environmental Chemical Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jece.2025.116201